Risk factors for surgical complications after anatomic lung resections in the era of VATS and ERAS. Issue 23 (24th October 2021) - Galata, Christian; Karampinis, Ioannis; Roessner, Eric D.; Stamenovic, Davor
Abstract: Background: The aim of this study was to identify risk factors for surgical complications after anatomic lung resections in the era of video‐assisted thoracic surgery (VATS) and enhanced recovery after surgery (ERAS). Methods: A retrospective analysis of all consecutive adult patients who underwent elective anatomic lung resections between January and December 2020 at our institution was performed. Results: Eighty patients (40 VATS, 40 thoracotomy) were included. The 30‐day mortality rate was 1.3%. The overall rate of major postoperative complications was 18.8%. Most major complications occurred in patients who underwent open surgery (complication rate 32.5%, share of total complications 86.7%). Major morbidity after VATS resection was rare (complication rate 2.5%, share of total complications 13.3%). In univariable analysis, thoracotomy ( p  = 0.003), impaired preoperative lung function ( p  = 0.003), complex surgery ( p  = 0.004) and sleeve resection ( p  = 0.037) were associated with adverse outcomes. In multivariable analysis, thoracotomy ( p  = 0.044) and impaired preoperative lung function ( p  = 0.028) were the only independent risk factors for major postoperative morbidity. Conclusion: Thoracotomy was associated with a 10‐fold increased risk for postoperative complications compared with minimally invasive surgery and was an independent risk factor for surgical complications. In the era of VATS and ERAS, the fact that thoracotomy is performed may be a reliable parameter to identify patients at risk for postoperative complications. Abstract : Complications after anatomic lung resections following an ERAS‐oriented protocol.